2019
DOI: 10.21061/jvs.v4i2.69
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Support: Analysis of an Online Discussion Forum for Significant Others of Deployed Service Members

Abstract: Military deployments can place stress on family members that can affect their physiological and psychological health. Although there has been much research on online social support in healthrelated groups, there is limited research on online social support in a deployment context. The researchers of this study conducted a content analysis of 151 discussion threads related to military deployments in an online forum for the significant others (SOs) of service members to examine the types of social support messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Accessing social support is a major driver of online activity (Qian & Mao, 2010), both on forums and services focused on specific needs or life-stages, and social media. This is particularly true for stressful life events, including health problems (Laranjo et al, 2015; Rui et al, 2013), living with disability (Braithwaite et al, 1999), pregnancy and new motherhood as an overseas Chinese immigrant (Mao et al, 2010; Qian & Mao, 2010), and military spouses during their partner’s deployment (Desens et al, 2019). It is also sought out by sexual assault survivors (Hosterman et al, 2018; Lowenstein-Barkai, 2020; Manikonda et al, 2018), and those suffering from stigmatized mental health conditions (De Choudhury & Kiciman, 2017; Ni et al, 2020).…”
Section: Online Social Support and Connective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessing social support is a major driver of online activity (Qian & Mao, 2010), both on forums and services focused on specific needs or life-stages, and social media. This is particularly true for stressful life events, including health problems (Laranjo et al, 2015; Rui et al, 2013), living with disability (Braithwaite et al, 1999), pregnancy and new motherhood as an overseas Chinese immigrant (Mao et al, 2010; Qian & Mao, 2010), and military spouses during their partner’s deployment (Desens et al, 2019). It is also sought out by sexual assault survivors (Hosterman et al, 2018; Lowenstein-Barkai, 2020; Manikonda et al, 2018), and those suffering from stigmatized mental health conditions (De Choudhury & Kiciman, 2017; Ni et al, 2020).…”
Section: Online Social Support and Connective Actionmentioning
confidence: 99%
“…Online social support takes a variety of forms. Cutrona and Suhr’s (1992) framework encompasses informational, emotional, social network, tangible, and esteem support and across a multitude of studies and contexts, informational and emotional types of social support occur most frequently (Desens et al, 2019; Qian & Mao, 2010; Rains et al, 2015; Rui et al, 2013). On social media, one meta-analysis found that the preference for informational support remained, but there was scant tangible support (Liu et al, 2018).…”
Section: Online Social Support and Connective Actionmentioning
confidence: 99%